Scientific mapping on Autism Spectrum Disorder in education through intellectual, social and conceptual analysis - Lorenzo Lledó, Gonzalo; Lorenzo-Lledó, Alejandro (Revista General de Información y Documentación, 2023)
In today's societies there is an increasing number of students with Specific Educational Support Needs in our classrooms. In recent years, an increasing presence of students with Autism Spectrum Disorder has been detected. Therefore, the objective is to analyze the evolution of scientific production on autism spectrum disorder using the bibliometric approach of scientific mapping based on the study of the intellectual, social and conceptual structure during the period 1969-2021. A search was carried out using the Web of Science database and the search terms were established using ERIC and Thesaurus. After applying the inclusion and exclusion criteria, 951 documents were obtained. The results show that from a thematic point of view both early intervention and intervention with new methodologies such as ICT are the current topics being worked on in the field. Also, the journals are grouped according to three lines of publication: psychology, special education, Education and Technology. Finally, APA (2013) and APA (2000) together with Horner et al., (2005) are the documents around which the document co-citation networks are grouped. As future lines of work, the possibility of using other analysis software to complement the information obtained is proposed.
Keywords: Austism Spectrum Disorder; Volution of scientific; Bibliometric